2012
DOI: 10.1038/tpj.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of asthma controller treatment

Abstract: The interpatient variability in response to asthma controllers is significant and associates with pharmacogenomic variability. The goal of the present study was to identify novel variants that associate with response to common asthma controllers: fluticasone, combination of fluticasone + salmeterol and montelukast with single nucleotide polymorphisms (SNPs) in β2-adrenergic receptor, corticosteroid and leukotriene pathway candidate genes. Participants in a large clinical trial of step-down strategies volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 49 publications
2
40
0
2
Order By: Relevance
“…Nevertheless, smaller studies by Mougey et al (n = 65 patients) [46] and Kotani et al (n=21 patients) [61] did not find any pharmacogenetics effect of this variant in studies with montelukast.…”
Section: Leukotriene Modifiers Responsementioning
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, smaller studies by Mougey et al (n = 65 patients) [46] and Kotani et al (n=21 patients) [61] did not find any pharmacogenetics effect of this variant in studies with montelukast.…”
Section: Leukotriene Modifiers Responsementioning
confidence: 77%
“…It has been hypothesized that variation in this gene influences the level of endogenous corticosteroid secretion and thereby alters the response to ICS. Several SNPs in this gene have been studied and two variants have been replicated at least once [30,46,47] in independent populations of children and adults with asthma; however, results have been inconsistent [48].…”
Section: Ics Responsementioning
confidence: 99%
“…Five markers in CRHR1 (rs 242941, rs 739645, rs 1876831, rs 1876829 and rs 1876828) showed significant association with change in % predicted of Forced Expiratory Volume in 1second (∆FEV1%pred), wherein rs242941 was associated with decreased FEV1%pred. 12 Moreover, rs 242941 was also studied as a biomarker for susceptibility to major depressive disorder (MDD) and fluoxetine response variation among Americans, Mexican-Americans and Chinese. [13][14][15][16][17] GLCCI1 gene (Glucocorticoid induced 1; Chromosomal locus: 7p21.3; NCBI Gene ID: 113263) with eight exons encodes a protein of unknown function which has induced expression by glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
“…7 Reported MAF of rs 242941 ('T') among Caucasian, Greece, Korean and North Indian populations were 0.34, 0.28, 0.08 and 0.26, respectively. 11,12,27 From above stated studies on genetic association with ICS response rate, it can be assumed that, carriers of rs 37972 ('T'), rs 28364072 ('G') and rs 242941 ('T') are associated with either decrement or no improvement in lung function in spite of treatment, thus poorly responding to ICS. From the present study findings we conclude that, minor allele frequencies of rs 242941, rs 28364072 and rs37972 were 0.51, 0.33 and 0.38, respectively in Tamilian population which were significantly different from various global populations.…”
mentioning
confidence: 99%
“…11,12 Traditional measures (eg, self-reported symptoms) are important to diagnose and monitor response to asthma treatment. 2,3,15,16 However, there have been few pharmacogenomic studies focusing on self-reported asthma symptoms, 17,18 although self-reported asthma symptoms account for a substantial proportion of the clinical measures of treatment response. 19,20 Therefore we performed a genome-wide association study (GWAS) with the hypothesis that we could identify novel genetic markers predicting symptomatic response to ICSs in asthmatic patients.…”
mentioning
confidence: 99%